2018
DOI: 10.1029/2018jc014223
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Local Wind and Ocean Circulation to the Interannual Variability in Coastal Upwelling Intensity in the Northern South China Sea

Abstract: Using in situ data, satellite observations, and model outputs, we analyzed the interannual variability in coastal upwelling intensity in the northern South China Sea. Comparing coastal upwelling observed from three cruises during the summers of 2008 and 2016, we found that coastal upwelling was stronger during 2016 compared to 2008, although the local upwelling favorable wind was stronger in 2008. The stronger near-bottom cross-shelf current and shallower thermocline in the slope resulted in stronger upwelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…More importantly, they depict the NIG reversals as possessing different nature and scientific relevance: either being a basic wind-induced circulation or, instead, representing a proper mode of oceanic variability. Note that phenomena from which such alternative behavior could emerge have been observed also in other regions of the World Ocean, which puts our investigation in a context of more general relevance [27][28][29] . A key step forward in our understanding of the BiOS, particularly towards establishing it as a mode of variability, regards thus whether interior ocean processes alone are capable of triggering reversals in the NIG circulation.…”
mentioning
confidence: 60%
“…More importantly, they depict the NIG reversals as possessing different nature and scientific relevance: either being a basic wind-induced circulation or, instead, representing a proper mode of oceanic variability. Note that phenomena from which such alternative behavior could emerge have been observed also in other regions of the World Ocean, which puts our investigation in a context of more general relevance [27][28][29] . A key step forward in our understanding of the BiOS, particularly towards establishing it as a mode of variability, regards thus whether interior ocean processes alone are capable of triggering reversals in the NIG circulation.…”
mentioning
confidence: 60%
“…However, in the MNCU and the YDCU, the temporal pattern of the upwelling index was different from that of SST_A or Chl-a increase, which may indicate that there were other factors contributing to the formation of these two coastal upwelling regions. It has been found that the coastal upwelling occurs off Shantou coast during wind relaxation [29], indicating that in addition to the local wind, there are other factors (e.g., topography, thermocline depth on the shelf) contributing to the formation of the MNCU or the YDCU [6,30]. Moreover, according to the in situ observations, the MNCU and the YDCU can uplift the deeper water to the layer of 10 m [31].…”
Section: Upwelling Index and Upwelling Mechanisms In The Nscsmentioning
confidence: 99%
“…Generally speaking, the upwelling strength increases from May, reaches the maximum in July, and then decreases to a minimum in September. This is because the coastal upwellings in the NSCS are mainly wind-driven and thus follow the inter-monthly patterns of the summer monsoon, although there are still other factors driving the MNCU and the YDCU [6,29,30]. The correlation coefficients of the monthly characteristics (duration in Figure 6a, influence area in Figure 8a, SST_A in Figure 9a, Chl-a increase in Figure 10a, and upwelling index in Figure 11a) are shown in Tables 1-3 for the Minnan coastal upwelling, the Yuedong coastal upwelling, and the Qiongdong coastal upwelling, respectively.…”
Section: Upwelling Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a well-developed broad continental shelf and a steep continental slope, the southwestern Taiwan Strait is one of the most important fishing grounds in China (Figure 1a). Affected by factors such as topography, monsoon, and Kuroshio intrusion, the southwestern Taiwan Strait has a variable circulation structure with a complex interaction among different currents (Guan, 1998;Hu et al, 2010;Liu et al, 2008;Shu et al, 2016Shu et al, , 2018aShu et al, , 2018bShu et al, , 2019Su, 2004). Major circulation systems in the southwestern Taiwan Strait include the South China Sea Warm Current (SCSWC, also known as the counter-wind current in the northern SCS), the South China Sea Branch of Kuroshio (SCSBK, also known as slope current in the northern SCS), and the coastal current (Hu et al, 2010;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%